Pemetaan Potensi Ekonomi dalam Upaya Meningkatkan Penyerapan Tenaga Kerja di Kota Surabaya - Mohammad Wahed (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
The purpose of this study is to analyze the economic potential in order to increase employment in the city of Surabaya. Compilation of mapping analysis of economic potential in employment in Surabaya will use two basic research designs, namely Exploratory and Descriptive Research which is carried out in stages. From the results of the calculation of the Location Quotient index (base and non basis), the Differential Shift component (internal growth component), and the Proportional Shift component (external growth component) as well as the sectoral typology of economic sectors explains that there are three potential sectors in the Surabaya City area namely: Transportation Sector, Accommodation Provision Sector, and Information Sector. While the economic sector according to the business field, the highest economic growth was achieved by the business of the Provision of Accommodation and Food and Drink followed by the growing Information and Communication business field and finally the Construction business field.